2019
DOI: 10.1039/c9ra07519d
|View full text |Cite
|
Sign up to set email alerts
|

Switched reaction specificity in polyesterases towards amide bond hydrolysis by enzyme engineering

Abstract: The constitution of a water network for the nitrogen inversion mechanism by H-bonding can increase amide-containing substrate acceptance of polyesterases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Based on the control experiments, we can identify HiC (specifically, Novozyme 51032) as the only promoter of the formation of the amide product. Amide formation catalyzed by cutinases has only been reported for Fusarium solani pisi cutinase and an engineered Humicola insolens cutinase; [37][38][39][40] the amidase/protease activity of commercial Novozyme 51032 (Humicola insolens cutinase expressed in Aspergillus oryzae) has not been reported. To get insight into the protease activity of Novozyme 51032, assays using an o-nitrophenyl amide model substrate (Scheme S1) were performed in 2 M glycine or 3 M Tris buffer at different pH values (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the control experiments, we can identify HiC (specifically, Novozyme 51032) as the only promoter of the formation of the amide product. Amide formation catalyzed by cutinases has only been reported for Fusarium solani pisi cutinase and an engineered Humicola insolens cutinase; [37][38][39][40] the amidase/protease activity of commercial Novozyme 51032 (Humicola insolens cutinase expressed in Aspergillus oryzae) has not been reported. To get insight into the protease activity of Novozyme 51032, assays using an o-nitrophenyl amide model substrate (Scheme S1) were performed in 2 M glycine or 3 M Tris buffer at different pH values (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…This could also be informative for enzymatic engineering. For example, critical enzymes of microbes for biofuel production and plastic degradation might need to tolerate some diversity in their substrates [ 56 ], while the key enzymes for biosynthesis would like to exclude promiscuity and only produce one product as pure as possible. The present study provides a relatively simple guideline for enzymatic engineering, e.g., reducing salt bridges for the former to increase its flexibility to accommodate different substrates while adding salt bridges for the latter to enhance its specificity and, probably, the enzymatic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Enabling catalytic promiscuity is a meaningful approach to expand the capacity of plasticdegrading enzymes to use different plastic substrates, especially for plastics with few enzymes known to efficiently degrade them (such as PAs and PUs) [94,95]. Recently, a pioneering study reported manipulation of the Thc_Cut1 cutinase to develop its promiscuous amidase activity towards depolymerizing artificial PAs [96]. The residues possibly obstructing the interaction of water molecules with the transition state were identified for mutation, which generated a 6-15-fold higher hydrolytic activity [96].…”
Section: Trends Trends In In Biotechnology Biotechnologymentioning
confidence: 99%
“…Recently, a pioneering study reported manipulation of the Thc_Cut1 cutinase to develop its promiscuous amidase activity towards depolymerizing artificial PAs [96]. The residues possibly obstructing the interaction of water molecules with the transition state were identified for mutation, which generated a 6-15-fold higher hydrolytic activity [96].…”
Section: Trends Trends In In Biotechnology Biotechnologymentioning
confidence: 99%